European consensus and the legitimacy of the European Court of Human Rights - Dzehtsiarou, Kanstantsin (Cambridge University Press, 2015)
"Has the European Court of Human Rights (ECtHR or Court) lost its legitimacy? The answer to this question is perhaps 'no'. If this was the case, the Contracting Parties would stop executing judgments of the Court; the applicants would stop bringing their complaints to the Court; and, finally, the Contracting Parties would denounce the European Convention on Human Rights (ECHR or Convention). Another option might be that the ECtHR would continue to exist without having any real impact on human rights standards in Europe and its judgments would lose much of their value. This has not yet happened. International tribunals, including the European Court of Human Rights (ECtHR), face a substantial structural deficiency; they operate within systems that lack the coercive capacity to enforce their judgments. International courts thus depend, to a greater degree than domestic courts, on the legitimacy of their judgments as a basis upon which to encourage, and in effect coerce, compliance"--